1975
DOI: 10.1080/09553007514550061
|View full text |Cite
|
Sign up to set email alerts
|

DNA-to-protein Cross-linking in Synchronized HeLa Cells Exposed to Ultra-violet Light

Abstract: The U.V.-induced DNA-to-protein cross-linking in synchronously growing HeLa cells exhibits age-dependent variations. The maximum yield of cross-linking is observed during S-phase and exposure of mid-S cells to 250 ergs/mm2 renders about 22 per cent of DNA unextractable owing to cross-linking with proteins. Cells irradiated in G1 or G2 exhibit much smaller amount of cross-linking. The unextracted DNA was recovered from the protein fraction, and the addition of 0-5 per cent trypsin solution rendered all the DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The amount of unextractable DNA maintained a constant value in cells incubated for periods of time up to ten hours after the termination of irradiation. Han et al (1975) studied the UV induction of DNA-protein cross-links in synchronized HeLa cells as a function of cell cycle phase. They found that the synchronized cells were most susceptible to cross-linking in S phase; cells irradiated in G1 or G2 phase displayed significantly decreased susceptibilities.…”
Section: Studies On Cellular Viral and Chromosomal Systemsmentioning
confidence: 99%
“…The amount of unextractable DNA maintained a constant value in cells incubated for periods of time up to ten hours after the termination of irradiation. Han et al (1975) studied the UV induction of DNA-protein cross-links in synchronized HeLa cells as a function of cell cycle phase. They found that the synchronized cells were most susceptible to cross-linking in S phase; cells irradiated in G1 or G2 phase displayed significantly decreased susceptibilities.…”
Section: Studies On Cellular Viral and Chromosomal Systemsmentioning
confidence: 99%
“…In general, it has been known that UV light produces various kinds of DNA lesions besides pyrimidine dimers, i.e. single strand breaks (Elikind and Han, 1978;Miguel and Tyrrell, 1983;Peak et al, 1987;Rosenstein and Ducore, 1983), DNA-protein crosslinks (Chiu et al, 1984;Fornace and Kohn, 1976;Han et al, 1975;Lai et al, 1987;Peak et al, 1985a,b), DNA double strand breaks (Bradley and Taylor, 1981) and thymine glycol (Hariharan and Cerutti, 1977). The present paper compares a number of measurements, including the repair of non-*To whom correspondence should be addressed.…”
Section: In T R 0 Duct I 0 Nmentioning
confidence: 97%
“…exposure during which lesions other than the pyrimidine dimer are accumulated . This second type of lesion could, for example, be a cross-link between DNA and protein of the type described by Han, Korbelik and Ban (1975) .…”
Section: Discussionmentioning
confidence: 99%